Emotions, technology, and social media - Tettegah, Sharon Y. (Academic Press, 2016)
"Emotions, Technology, and Social Media discusses the ways the social media sphere uses emotion and technology, and how each of these has become part of the digital culture. The book explores this expression within a psychological theoretical framework, addressing feelings about social media, and its role in education and knowledge generation. The second section investigates the expression of feelings within social media spaces, while subsequent sections adopt a paradigm of active audience consumption to use social media to express feelings and maintain social connectivity."--
Includes bibliographical references and index
Keywords: PSYCHOLOGY / Social Psychology; Emotions; Information technology / Psychological aspects; Information technology -- Psychological aspects; Online social networks -- Psychological aspects; Social media -- Psychological aspects